2008
DOI: 10.1111/j.1365-2796.2008.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation / Perfusion SPECT for diagnostics of pulmonary embolism in clinical practice

Abstract: Aim. The aim of this retrospective study is to illustrate clinical utility and impact of pulmonary embolism (PE) diagnostics of up to date Ventilation ⁄ Perfusion SPECT (V ⁄ P SPECT ) applying holistic interpretation criteria.Material and methods. During a 2-year period 2328 consecutive patients referred to V ⁄ P SPECT for clinically suspected PE were examined. Final diagnosis was established by physicians clinically responsible for patient care. To establish the performance of V ⁄ P SPECT negative for PE, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
0
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(189 citation statements)
references
References 23 publications
(26 reference statements)
5
168
0
16
Order By: Relevance
“…CTPA may be a financially suboptimal choice if employed as the first‐line imaging choice for the entire imaging population. Furthermore, some studies have estimated that CTPA may be contraindicated in up to 50% of the suspected PE imaging directed population because of an underlying clinical condition including renal insufficiency, recent myocardial infarction, grave arrhythmia, allergy, etc 27. Without this contrast‐related burden, CTPA fares very well against planar and SPECT with incremental PPPM cost savings of $2,587.30 and $456.50, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CTPA may be a financially suboptimal choice if employed as the first‐line imaging choice for the entire imaging population. Furthermore, some studies have estimated that CTPA may be contraindicated in up to 50% of the suspected PE imaging directed population because of an underlying clinical condition including renal insufficiency, recent myocardial infarction, grave arrhythmia, allergy, etc 27. Without this contrast‐related burden, CTPA fares very well against planar and SPECT with incremental PPPM cost savings of $2,587.30 and $456.50, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, V/P SPECT permits one to identify patterns typical of other disorders such as chronic obstructive pulmonary disease (COPD), pneumonia and left heart failure. A broad V/P SPECT study showed that this is possible in the vast majority of cases [10].…”
Section: Basis For Good Clinical Practice: Guidelinesmentioning
confidence: 99%
“…In the PIOPED II study the positive predictive value for a PE within a lobar pulmonary artery was 97 % but fell to 68 % and 25 % at the segmental and subsegmental levels, respectively. Bajc et al and a prospective study by Gutte et al showed that V/P SPECT has higher sensitivity and specificity and less non-diagnostic findings than MDCT [10,14]. A recent study by Mahdavi et al showed that in the presence of an indeterminate CT angiography (CTA) in patients with high clinical suspicion of PE, V/P SPECT often provides a diagnosis [15].…”
Section: Comparison With Mdctmentioning
confidence: 99%
“…Kriterlere göre hastalar normal, düşük, orta ve yüksek olasılıklı olarak sınıflandırılmıştır. Klinisyenler ile iletişimi kolaylaştırmak için, üç katmanlı sınıflandırma tercih edilir: Normal tarama (APE dışlar), yüksek olasılık tarama (çoğu hastada APE olarak kabul edilir) ve tanısal olmayan tarama (15,16). Prospektif klinik çalışmaların sonucunda normal bir perfüzyon sintigrafisi olan hastalarda antikoagülan tedavinin kesilmesinin güvenli olduğunu ileri sürmüş ve V / P sintigrafisi ile BT taramanın karşılaştırıldığı randomize çalışmalar tarafından doğrulanmıştır (15).…”
Section: Direkt Katater Pulmoner Anjiografiunclassified